Climate change and interconnected risks to sustainable development in the Mediterranean. Issue 11 (November 2018) - Cramer, Wolfgang; Guiot, Joël; Fader, Marianela; Garrabou, Joaquim; Gattuso, Jean-Pierre; Iglesias, Ana; Lange, Manfred; Lionello, Piero; Llasat, Maria; Paz, Shlomit; Peñuelas, Josep; Snoussi, Maria; et al.
Abstract Recent accelerated climate change has exacerbated existing environmental problems in the Mediterranean Basin that are caused by the combination of changes in land use, increasing pollution and declining biodiversity. For five broad and interconnected impact domains (water, ecosystems, food, health and security), current change and future scenarios consistently point to significant and increasing risks during the coming decades. Policies for the sustainable development of Mediterranean countries need to mitigate these risks and consider adaptation options, but currently lack adequate information — particularly for the most vulnerable southern Mediterranean societies, where fewer systematic observations schemes and impact models are based. A dedicated effort to synthesize existing scientific knowledge across disciplines is underway and aims to provide a better understanding of the combined risks posed. Climate change, in combination with existing environmental issues, threatens the Mediterranean region. This Review highlights how climate change will interact with other factors to exacerbate five areas of risk unless there is mitigation and adaptation.